Wear Performance of Laser Processed Tantalum Coatings - Dittrick, Stanley (2011)
This first generation investigation evaluates the in vitro tribological performance of laser-processed Ta coatings on Ti for load-bearing implant applications. Linear reciprocating wear tests in simulated body fluid showed one order of magnitude less wear rate, of the order of 10(−4)mm(3)(N.m)(−1), for Ta coatings compared to Ti. Our results demonstrate that Ta coatings can potentially minimize the early-stage bone-implant interface micro-motion induced wear debris generation due to their excellent bioactivity comparable to that of hydroxyapatite (HA), high wear resistance and toughness compared to popular HA coatings.